The use of pediatric logistic organ dysfunction (PELOD) scoring system to determine the prognosis of patients in pediatric intensive care units - Dewi Metta; Dedi Soebardja; Dadang Hudaya S (Paediatrica Indonesiana, 2006)
Background Prediction of outcome of patients admitted to pediat-ric intensive care unit (PICU) requires an objective tool for measure-ment. It is important to provide information for the patient’s familyand to explain the objectives of intensive care.Objective To evaluate whether the Pediatric Logistic Organ Dys-function (PELOD) scoring system can be used to determine the prog-nosis of patients treated in PICU.Methods A longitudinal-observational study on patients treated inthe PICU of Hasan Sadikin General Hospital was conducted in No-vember 2004-December 2004. The PELOD scoring system wasapplied to all subjects within the first 24 hours of PICU admission.The scoring system consists of physical and laboratory variables of6 organs, namely neurological, cardiovascular, renal, respiratory,hematological, and hepatic systems. The sum of scores were ana-lyzed by logistic regression method to calculate the probability ofdeath. The subjects were monitored until they passed away or weredischarged from PICU.Results There were 32 subjects who met the inclusion criteria. Themean (SD) of PELOD scores in survivors was 13.5 (8.5) and in nonsurvivors was 22.2 (10.1) (Z M-W =-2.507;P=0.012), while the meanof PELOD scores in survivors of PELOD scores validation studywas 31.0, and in non survivors was 9.4. The increase of PELODscores correlated with the increase in the probability of death(P=0.038), and a linear regression chart showed a positive correla-tion (R 2 =0.93). PELOD scores at a 50% probability of death was 20,while the mean PELOD scores validation study was 26. Based onthe probability of death of P<0.5, the death prediction and observeddeath had a sensitivity of 54.5% and a specificity of 80.9%. Amongpatients with high PELOD scores (>20) and those with low PELODscores (<20), the number of patients who survived with extendedlength of stay in PICU, were not significantly different (P=0.15).Conclusions PELOD scoring system can be used to determine thepatient’s probability of death in PICU, but can not be used to predictthe length of stay in PICU